Bridging the extracellular vesicle knowledge gap: insights from non-mammalian vertebrates, invertebrates, and early-diverging metazoans - Liegertová, Michaela; Janoušková, Olga (Frontiers in Cell and Developmental Biology, 2023)
Extracellular vesicles (EVs) are lipid-enclosed structures that facilitate intercellular communication by transferring cargo between cells. Although predominantly studied in mammals, extracellular vesicles are ubiquitous across metazoans, and thus research in non-mammalian models is critical for fully elucidating extracellular vesicles biology. Recent advances demonstrate that extracellular vesicles mediate diverse physiological processes in non-mammalian vertebrates, including fish, amphibians, and reptiles. Piscine extracellular vesicles promote fin regeneration in zebrafish and carry heat shock proteins regulated by stress. Frog extracellular vesicles containing microRNAs modulate angiogenesis, while turtle extracellular vesicles coordinate reproductive functions. Venom from snakes contains extracellular vesicles that mirror the whole venom composition and interact with mammalian cells. Invertebrates also possess extracellular vesicles involved in immunity, development, and pathogenesis. Molluscan extracellular vesicles participate in shell formation and host interactions. Arthropod models, including Drosophila, genetically dissect conserved pathways controlling extracellular vesicles biogenesis and signalling. Nematode extracellular vesicles regulate larval development, animal communication, and ageing via conserved extracellular vesicles proteins. Ancient metazoan lineages utilise extracellular vesicles as well, with cnidarian extracellular vesicles regulating immunity and regeneration. Ultimately, expanding extracellular vesicles research beyond typical biomedical models to encompass phylogenetic diversity provides an unparalleled perspective on the conserved versus specialised aspects of metazoan extracellular vesicles roles over ∼500 million years. With a primary focus on the literature from the past 5 years, this review aims to reveal fundamental insights into EV-mediated intercellular communication mechanisms shaping animal physiology.